AGE-RELATED CHANGES IN RENAL RESISTIVE INDEX AFTER ESWL - Hermawan, Anton; Alif, Sabilal; djatisoesanto, wahjoe; Wulanhandarini, Tri; Budiono, Budiono (Indonesian Journal of Urology, 2014)
Objective: To determine relation between age and resistive index (RI) changes occurring after extracorporeal shock wave lithotripsy (ESWL). Material & Method: We performed a prospective study in Soetomo Hospital Surabaya. Using duplex ultrasonography, RI was determined in 20 patients with calyceal kidney calculi and pelvic kidney calculi. RI of the interlobar renal arteries were measured in the region near the calculi (distance, less than 2 cm), one hour before ESWL and RI was measured again at 1 hour, 3 days and 7 days after ESWL. Changes in RI values and relation with age (≤ 60 years old and > 60 years old) were evaluated. Results: The renal RI increased significantly 1 hour and 3 days after ESWL, but returned to before ESWL values 7 days after ESWL in the both groups. Although there was positive correlation between age and RI before ESWL, but there was no correlation between age and RI changes after ESWL. Conclusion: Renal RI is higher with age > 60 years, after ESWL renal RI showed transient increase which returned to baseline after 7 days.Key words: Color Doppler Ultrasonography, extracorporeal shock wave lithotripsy, renal resistive index, calyceal kidney calculi, pelvic kidney calculi.